PENERAPAN ALGORITMA K-MEANS CLUSTERING DALAM PROSES PENGELOMPOKAN KASUS MENINGGAL DUNIA COVID-19 DI INDONESIA - Rizki Entis Sutisna (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The country of Indonesia is still struggling with the Covid-19 outbreak to date, the same as other countries in the world. The number of Covid-19 cases in Indonesia every day continues to increase along with the recovery rate, but not a few also die. The Indonesian government provides socialization to the public to carry out physical distancing to break the chain of the spread of COVID-19 which is spreading in various parts of Indonesia. Therefore, there must be a lot of data collection, from that much data we can see patterns in determining the grouping of the spread of Covid-19 based on tests using the k-means clustering algorithm. The result of the research is to know the area that has the highest death rate. And making decisions for areas with a high death rate will be included in the red zone and action must be taken immediately.